The UK's withdrawal from the EU : a legal analysis - Dougan, Michael (Law professor) (Oxford : Oxford University Press, 2021)
Following a national referendum on 23rd June 2016, the UK announced its intention to end its decades-long membership of the EU, perhaps the most dramatic and important change in national policy since 1945. That decision initiated a process of complex negotiations aimed at making the arrangements required for an 'orderly Brexit'. 'The UK's Withdrawal from the EU' explores the UK's departure from the EU from a legal perspective: Michael Dougan provides a critical analysis of the final EU-UK Withdrawal Agreement, including explorations of the future protection of citizens' rights, the border between Ireland and Northern Ireland, and the prospects for future EU-UK relations in fields such as trade and security. These explorations also include an analysis of the primary problems that arose during the Brexit negotiation process and various constitutional principles relevant to EU withdrawal law.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 7, 2021).
Keywords: Great Britain; European Union -- Great Britain; Great Britain -- Relations -- European Union countries; European Union countries -- Relations -- Great Britain